Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12913-015-0758-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intensive healthcare waste management training model among health professionals at teaching hospitals of Pakistan: a quasi-experimental study

Abstract: BackgroundInfectious waste management has always remained a neglected public health problem in the developing countries, resulting in high burden of environmental pollution affecting general masses. Health workers are the key personnel who are responsible for the management of infectious waste at any hospital, however, their proper training and education is must for an optimal performance. This interventional study was conducted to assess the effectiveness of Intensive healthcare waste management (IHWM) traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 14 publications
(14 reference statements)
6
36
0
3
Order By: Relevance
“…This low percentage could be due to limited budgetary allocation which does not permit organization of such events. A recent study by Kumar et al (2015) suggested an intensive healthcare waste management training as an effective intervention for improving knowledge, attitudes and practices among healthcare workers regarding healthcare waste management. Other studies (Kumar et al, 2016;Abah, 2011) have also indicated regular training of health care workers on waste management to have a great role on their practices on waste management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low percentage could be due to limited budgetary allocation which does not permit organization of such events. A recent study by Kumar et al (2015) suggested an intensive healthcare waste management training as an effective intervention for improving knowledge, attitudes and practices among healthcare workers regarding healthcare waste management. Other studies (Kumar et al, 2016;Abah, 2011) have also indicated regular training of health care workers on waste management to have a great role on their practices on waste management.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing concern on medical waste management, some developing countries have recently implemented interventions that have improved their waste management practices (Kumar et al, 2015;Tabash et al, 2016;Awodele et al, 2016). Although, there is very limited information on health care waste management in Cameroon, few studies conducted report medical waste management as a challenge in both primary and tertiary care facilities (Doumtsop, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Here, it is important to note that in Table 4, we selectively presented the results in the measuring unit of kg bed -1 day -1 , while other measuring units were not considered. Multiple studies have also used many other measuring units such as kg patient -1 day -1 (Alves et al, 2014;Gören and Ozdemir, 2011;Mugambe et al, 2012;Nemathaga et al, 2008;Sawalem et al, 2009), kg day -1 (Idowu et al, 2013;Manga et al, 2011; Moreira and Günther, Gai et al, 2009Gai et al, , 2010Yong et al, 2009;Zhang et al, 2013 2 India Athavale and Dhumale, 2010;Babu et al, 2009;De and Debnath, 2016;Gupta and Boojh, 2006;Hanumantha Rao, 2009;Mohankumar and Kottaiveeran, 2011;Nema et al, 2011;Onursal, 2003;Patil and Pokhrel, 2005;Rao, 2009;Verma et al, 2008 3 Pakistan Ali et al, 2015Ali et al, , 2016Jaffer, 2013;Kemu, 2011Kemu, , 2014Khattak, 2009;Kumar et al, 2010;Kumar et al, 2015a;Kumar et al, 2016;Kumar et al, 2015b;Qaiser, 2012;Sabiha-Javied et al, 2008;Shahida Rasheed SI, 2005;Sobia et al, 2014 4 Bangladesh Alam et al, 2008;Hassan et al, 2008;…”
Section: Generationmentioning
confidence: 99%
“…Hospital waste is known as second most dangerous waste in the world that should be managed properly by well skilled staff. Hospital waste is produced during the patient care, in clinics, maternity homes and research institutes 2 . Currently, there has been renewed focus by the patients, communities and providers about the management of healthcare waste all over the world 3 .…”
Section: Introductionmentioning
confidence: 99%